Modulation of the selectivity of immobilized lipases by chemical and physical modifications: Release of omega-3 fatty acids from fish oil - Fernández-Lorente, Gloria; Betancor, Lorena; Carrascosa, Alfonso V.; Palomo, José Miguel; Guisán, José Manuel (Journal of the American Oil Chemists' Society, 2012)
Three different lipases (from Candida antarctica fraction B (CALB), Thermomyces lanuginose (TLL), and Rhizomucor miehei (RML)) were immobilized by two different methods, immobilization on CNBr-activated Sepharose via a mild covalent immobilization or adsorption onto hydrophobic supports (Octyl-Sepharose). These immobilized preparations were chemically and physically modified on the protein surface (enzyme carboxylic groups with ethylenediamine, amino groups with succinic anhydride, or coating with polyethyleneimine).The activity and selectivity in the production of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) by enzymatic hydrolysis of sardine oil were evaluated. Activity and selectivity were dependent on the different lipases, the immobilization protocols, the modification methods, and the pH of the reaction media. The selectivity (EPA/DHA ratio) of RML immobilized on CNBr-activated Sepharose was increased after succinylation from 7.5 to 34 at pH 6.0. The selectivity of octyl-RML improved from 1.5 to 8.5 when pH was increased from 6 to 8. The selectivity and activity of octyl-TLL increased twofold after PEI coating at pH 6. The properties of CAL-B derivatives were slightly altered after modification. © 2011 AOCS. This work was sponsored by the Spanish Ministry of Science and Innovation (AGL-2009-07526) and the Intramural project (200980I133). We gratefully recognize the Spanish Ministry of Science and Innovation for the ‘‘Ramón y Cajal’’ contract for Dr. Fernandez-Lorente. Peer Reviewed